THE ROLE OF THE FAMILY IN INSTILLING ISLAMIC-BASED BUSINESS ETHICS IN CHILDREN - Karimullah, Suud Sarim; Efendi, Bahtiar; Sattar, Sattar; Ningsih, Tri Widyastuti (Universitas Nurul Jadid, 2023)
This study reveals the role of the family in instilling Islamic-based business ethics in children properly by the teachings of Islam. This study adopts the literature study method conducted with integrative literature analysis to obtain comprehensive and in-depth results related to the role of the family in the education of Islamic-based business ethics in children. By combining and synthesizing findings from a variety of relevant literature sources, this method enables a holistic and thorough investigation of this topic. The findings of this study state that families play a key role in shaping Islamic-based business ethics in children, which in turn contributes to the formation of ethical and sustainable business leaders in the future. The influence of the family on the development of children's business ethics covers various aspects, from risk management to stakeholder responsibility, as well as commitment to corporate social responsibility. In this context, the family serves as a role model and teaches children to conduct business with integrity, which will ultimately help create a generation of ethical, sustainable businesses that contribute positively to society and the environment.